2004
DOI: 10.1139/g04-027
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a family of resistance gene analogue sequences of the nucleotide binding site (NBS) type fromLensspecies

Abstract: Most known plant disease-resistance genes (R genes) include in their encoded products domains such as a nucleotide-binding site (NBS) or leucine-rich repeats (LRRs). Sequences with unknown function, but encoding these conserved domains, have been defined as resistance gene analogues (RGAs). The conserved motifs within plant NBS domains make it possible to use degenerate primers and PCR to isolate RGAs. We used degenerate primers deduced from conserved motifs in the NBS domain of NBS-LRR resistance proteins to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 55 publications
4
35
0
17
Order By: Relevance
“…The DNA-based markers, such as RFLP (Havey and Muehlbauer, 1989;Muench et al, 1991;Rajora and Mahon, 1994), RAPD (Sharma et al, 1995;Ferguson et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009;Tewari et al, 2012), AFLP (Sharma et al, 1996;Zavodna et al, 2000;Duran and Perez de le Vega, 2004;Kahraman et al, 2004;Rubeena et al, 2006;Fiocchetti et al, 2009;Toklu et al, 2009), microsatellite markers (Duran and Perez de le Hamwieh et al, 2009;Liu et al, 2008;Babayeva et al, 2009;Reddy et al, 2010;Gupta et al, 2012, Tewari et al, 2012Zaccardelli et al, 2012), inter simple sequence repeat (ISSR) (Zavodna et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009), internal transcribed spacers (ITS) (Fernandez et al, 2000;Mayer and Bagga, 2002;Sonnante et al, 2003), non-transcribed spacer (NTS) (Fernandez et al, 2005), sequenced tagged microsatellite site (STMS) (Inder et al, 2008;Datta et al, 2011), single-nucleotide polymorphisms (SNPs) (Alo et al, 2011), and resistance gene analogue (RGA) (Yaish et al, 2004;Sari et al, 2013) were used to analyze phylogenetic relationships among taxa in the genus Lens, as well as the genetic diversity of cultivated lentil.…”
Section: Genus Lens Millermentioning
confidence: 99%
“…The DNA-based markers, such as RFLP (Havey and Muehlbauer, 1989;Muench et al, 1991;Rajora and Mahon, 1994), RAPD (Sharma et al, 1995;Ferguson et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009;Tewari et al, 2012), AFLP (Sharma et al, 1996;Zavodna et al, 2000;Duran and Perez de le Vega, 2004;Kahraman et al, 2004;Rubeena et al, 2006;Fiocchetti et al, 2009;Toklu et al, 2009), microsatellite markers (Duran and Perez de le Hamwieh et al, 2009;Liu et al, 2008;Babayeva et al, 2009;Reddy et al, 2010;Gupta et al, 2012, Tewari et al, 2012Zaccardelli et al, 2012), inter simple sequence repeat (ISSR) (Zavodna et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009), internal transcribed spacers (ITS) (Fernandez et al, 2000;Mayer and Bagga, 2002;Sonnante et al, 2003), non-transcribed spacer (NTS) (Fernandez et al, 2005), sequenced tagged microsatellite site (STMS) (Inder et al, 2008;Datta et al, 2011), single-nucleotide polymorphisms (SNPs) (Alo et al, 2011), and resistance gene analogue (RGA) (Yaish et al, 2004;Sari et al, 2013) were used to analyze phylogenetic relationships among taxa in the genus Lens, as well as the genetic diversity of cultivated lentil.…”
Section: Genus Lens Millermentioning
confidence: 99%
“…Mechanisms like duplication, unequal crossing over, ectopic recombination, gene conversion, and diversifying selection have been proposed to contribute to the structure of R gene clusters and the evolution of resistance specificities (Michelmore and Meyers, 1998;Young, 2000;Sun et al, 2001). Moreover, the presence of conserved motifs primarily within the NBS domain has been used extensively to identify resistance genes homologs in model and crop species (Kanazin et al, 1996;Aarts et al, 1998;Penuela et al, 2002;Zhu et al, 2002;Ferrier-Cana et al, 2003;Yaish et al, 2004;Palomino et al, 2006). In species where R genes have been studied, this pattern of widespread multigene clusters is common (Young, 2000;Hulbert et al, 2001;Meyers et al, 2003).…”
mentioning
confidence: 99%
“…In this study, of the 10 RGAs identified, seven were characterized as belonging to the non-TIR-NBS-LRR subclass. In contrast, relatively more TIR-NBS class RGAs have been reported in the cowpea (Bhavani et al, 2002), lentil (Yaish et al, 2004), and soybean (Kanazin et al 1996). …”
Section: Discussionmentioning
confidence: 97%
“…Using degenerate primers to isolate resistance gene analogs from different plant species has so far been an effective strategy (Yaish et al, 2004;Palomino et al, 2006;Bouktila et al, 2014). In the present study, we identified and characterized 10 RGAs in three pea varieties, using four primer combinations designated from G. max (Kanazin et al, 1996) and S. tuberosum (Leister et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation